ANALISIS GANGGUAN DIRECT SPEECH (DS) PADA KOMUNIKASI AIR TRAFIC CONTROL (ATC) DI PERUM LPPNPI KANTOR CABANG PALEMBANG - Ayub Wimatra; Muhammad Caesar Akbar; Alfiq Masjulianda (Penerbit Lafadz Jaya, 2023)
The objective of this research is to analyse the interference of Direct Speech (DS) in Air Traffic Control (ATC) communication at Perum LPPNPI Palembang Branch Office. The research method used is descriptive qualitative, relying on primary data obtained directly from the research location. This method allows for comprehensive documentation of the various aspects that influence DS interference in the interaction between ATC and pilots. Primary data was collected through direct observation, interviews with Air Traffic Controllers (ATCo), and analysis of DS communication recordings. The analysis identified the types of disruptions that occur, the factors that cause them, and their impact on flight safety and efficiency. These findings are described in detail in the context of the operational situation at the Palembang Branch Office. The research is expected to provide a comprehensive overview of the state of DS communications in the region and suggest ways to overcome or prevent disruptions. The practical implications of this study include recommendations for improving systems, training personnel, and implementing air traffic management policies. In conclusion, this research contributes significantly to enhancing the safety and efficiency of flight operations at Palembang Branch Office. It can serve as a valuable reference for future research in this field.